Analysis of the Strategy for Development of the Thousand Stone Semliro Tourist Attraction in Rahtawu Village - Muhammad Jodi Prasetiyo; Mohammad Ilham Zaki Zakaria; Istiqomatul Mutmainah; Ananda Siska Khoirunnisa; Kuswaningsih; Evi Wahyuningtyas; Ahmad Fatah (JURNAL PENDIDIKAN IPS, 2023)
The aim of this research is to determine the strategy for developing the Seribu Batu Semliro tourist attraction in Rahtawu Village. The Thousand Stones Semliro Tourist Attraction is one of the tourist attractions on the slopes of Mount Muria, Kudus Regency, namely in Rahtawu Village. This research uses descriptive qualitative methods with data sources originating from observations, interviews and documentation. The research results show that promotional activities are still lacking and tourist attractions are far from urban areas. The results of the SWOT analysis are as follows: 1) strength, namely the uniqueness of this tourist spot in the highlands of the Kudus area; 2) weakness, namely the factor that the road access to the Seribu Batu Semliro tourist attraction is still not good; 3) opportunity, namely revitalizing the economy of the surrounding community; 4) threats, which are prone to landslides during the rainy season which results in a lack of visitors. From the results of the analysis it can be concluded that the branding strategy is the most appropriate to use for developing the Seribu Batu Semliro tourist attraction.